The Empirics of Agglomeration Economies - Pierre-Philippe Combes; Laurent Gobillon (Institute for the Study of Labor (IZA), 2014)
We propose an integrated framework to discuss the empirical literature on the local determinants of agglomeration effects. We start by presenting the theoretical mechanisms that ground individual and aggregate empirical specifications. We gradually introduce static effects, dynamic effects, and workers' endogenous location choices. We emphasise the impact of local density on productivity but we also consider many other local determinants supported by theory. Empirical issues are then addressed. Most important concerns are about endogeneity at the local and individual levels, the choice of a productivity measure between wage and TFP, and the roles of spatial scale, firms' characteristics, and functional forms. Estimated impacts of local determinants of productivity, employment, and firms' locations choices are surveyed for both developed and developing economies. We finally provide a discussion of attempts to identify and quantify specific agglomeration mechanisms.
Keywords: R12; R23; J31; 330; agglomeration gains; density; sorting; learning; location choices